Non-coding RNAs as key players in neurodegeneration and brain tumors: Insights into therapeutic strategies - Mohamed Javad Saadh; Sarraa Ahmad Qahtan; Rafid Jihad Albadr; Gaurav Sanghvi; Rangaswamy Roopashree; Aditya Kashyap; A. Sabarivani; Jasur Rizaev; Waam Mohammed Taher; Mariem Alwan; Mahmod Jasem Jawad; Ali M. Ali Al-Nuaimi (Iranian Journal of Basic Medical Sciences, 2025)
Non-coding RNAs (ncRNAs), including microRNAs (miRNAs), long non-coding RNAs (lncRNAs), and other ncRNA types, have emerged as key regulators in neurodegenerative diseases and brain tumors. This review aims to provide insights into the role of ncRNAs in these conditions and their potential as diagnostic and therapeutic targets. We systematically reviewed literature from databases such as PubMed, Scopus, and Web of Science, applying specific inclusion and exclusion criteria to ensure comprehensive coverage of recent advancements. Although ncRNAs are involved in a range of molecular pathways, challenges in clinical translation, including specificity, cost, and validation, persist. This review highlights innovative strategies to overcome these barriers and promote the clinical application of ncRNAs. Moreover, we explore the emerging role of extracellular vesicle-enriched ncRNAs as cell-free therapeutic options for neurodegenerative diseases. The findings presented here emphasize the need for robust validation and the development of specific ncRNA-based treatments.